54.7k views
5 votes
Which expression is equivalent to 9x - (x – 3)(x + 1) + 10x?

-x2 + 19x+8
O -x2+26x+8
8x2+ 10x+8
8x2 + 26x+8

2 Answers

4 votes

Answer:

9x - (x-3)(x+1) +10x

Solving (x-3)(x+1) first

it implies x(x+1) -3 (x+1)

= x^2 + x - 3x -3

= x^2 -2x - 3

return the result into the original question

it gives: 9x - ( x^2 -2x -3) +10x

expand

9x - x^2 +2x+3+ 10x

collect the like terms

- x^2 +21x +3

Explanation:

User Reema
by
5.0k points
5 votes

Answer:

-x^2 + 21x + 3.

Explanation:

9x - (x – 3)(x + 1) + 10x

= 19x - (x^2 - 2x - 3)

= -x^2 + 2x + 19x + 3

= -x^2 + 21x + 3.

User Wdg
by
5.7k points